Correction: Fossil and Genetic Evidence for the Polyphyletic Nature of the Planktonic Foraminifera "Globigerinoides", and Description of the New Genus Trilobatus. - Silvia Spezzaferri (Public Library of Science (PLoS), 2021)
[This corrects the article DOI: 10.1371/journal.pone.0128108.].